A prospective study on efficacy of topical bupivacaine in split skin grafting donor site in immediate postoperative pain relief - Srikanth Vasudevan; Sudarshan Reddy Nagireddy; Ashok Basur Chandrappa; Y N Anantheshwar; Ritu Batth; Harish Kumar Kablian; Dinkar Sreekumar (Wolters Kluwer Medknow Publications, 2020)
Objective: The objective of this study was to compare the effectiveness of bupivacaine-soaked gauze dressing and conventional dressing for pain relief in patients requiring split-thickness skin graft for reconstruction of various defects. Methodology: Fifty patients requiring split-thickness skin grafting for various soft-tissue defects were divided into two groups with 25 patients in each group. In Group A, skin graft donor site dressing was kept moist with 10 mL/100 cm2 of 0.25% bupivacaine solution-soaked gauze, and in Group B, dressing was moistened with the same amount of normal saline-soaked gauze. Outcome was measured by comparing pain scores and calculating rescue analgesia requirements in the two groups in the first 24 h. Significance was determined by comparing analgesia-sparing effect of each dressing using Chi-square test. Results: In Group A, 1 out of 25 (4%) patients required rescue analgesia. In Group B, 23 out of 25 (92%) patients required rescue analgesia (P < 0.0001). There was 96% effectiveness of bupivacaine-soaked dressing while only 8% effectiveness of conventional dressing. Conclusion: Bupivacaine-soaked dressing should be considered as a potent alternative to traditional saline dressings for the skin graft donor site.